Prognostic relevance of caspase 8 -652 6N InsDel and Asp302His polymorphisms for breast cancer. Issue 1 (December 2016) - Kuhlmann, J.; Bankfalvi, A.; Schmid, K.; Callies, R.; Kimmig, R.; Wimberger, P.; Siffert, W.; Bachmann, H.
Abstract Background The minor allele of two caspase 8 polymorphisms, namelyCASP8 -652 6N InsDel (rs3834129) andCASP8 Asp302His (rs1045485), were repeatedly associated with reduced breast cancer susceptibility. Contrarily, the presence of the -652 6N Del or theCASP8 302His variant was reported to be an unfavorable prognostic factor in colorectal cancer or neuroblastoma. However, prognostic relevance of these genetic variants for breast cancer is completely unknown and is therefore adressed by the current study. Methods Genotyping was performed by pyrosequencing. Caspase 8 mRNA expression was quantified by comparative RT-qPCR. Results We observed an allele-dose dependent association betweenCASP8 -652 6N InsDel and caspase 8 mRNA expression in breast cancer tissue, with homozygous deletion carriers showing lowest relative caspase 8 expression (p  = 0.0131). Intriguingly, the presence of the -652 6N Del or the 302His variant was shown to be a negative prognostic factor for breast cancer in terms of an allele-dose dependent influence on overall survival (OS, p  = 0.0018, p  = 0.0150, respectively). Moreover, both polymorphisms were independent predictors of OS after adjusting for co-variats (p  = 0.007, p  = 0.037, respectively). Prognostic relevance of both polymorphisms were confirmed to be independent from each other and combined analysis of diplotypes revealed an additive influence upon OS (p  = 0.0002). Conclusion This is the first report, showing negative and independent prognostic impact of theCASP8 -652 6N Del and the 302His variant for breast cancer. Our data provide rationale to further validate clinical utility of these polymorphisms for breast cancer and to extend this investigation to a broad scope of other malignancies.